2019
DOI: 10.2298/pac1904387s
|View full text |Cite
|
Sign up to set email alerts
|

Giant dielectric response in microwave processed CaCu3Ti4O12 ceramics: A correlation among microstructure, dielectric and impedance properties

Abstract: Polycrystalline CaCu 3 Ti 4 O 12 (CCTO) ceramics was synthesized by microwave assisted solid-state reaction. Effect of sintering at different temperatures on the crystal structure, dielectric and impedance properties was investigated in detail. Rietveld analysis of X-ray diffraction data identified that crystal structure was a mixture of cubic CCTO and monoclinic CuO phases. Lattice parameters and amount of CuO secondary phase were also estimated as a function of sintering temperature. Microstructural investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Broad peaks indicating dielectric anomalies were observed in all the investigated composites, shifting to higher temperatures with increasing applied frequencies. This behavior is charac-teristic of relaxor ferroelectrics and is associated with diffuse phase transition behavior [256]. It was demonstrated that the temperature dependence of ε 1 in composites is influenced by the dielectric behavior of HA, BZT-BCT, and intermediate phases present in the composite materials.…”
Section: Dielectric Constantmentioning
confidence: 96%
“…Broad peaks indicating dielectric anomalies were observed in all the investigated composites, shifting to higher temperatures with increasing applied frequencies. This behavior is charac-teristic of relaxor ferroelectrics and is associated with diffuse phase transition behavior [256]. It was demonstrated that the temperature dependence of ε 1 in composites is influenced by the dielectric behavior of HA, BZT-BCT, and intermediate phases present in the composite materials.…”
Section: Dielectric Constantmentioning
confidence: 96%